ASPEK PENDIDIKAN KARAKTER DALAM PUISI HAMKA - Solihati, Nani (LITERA, 2017)
Abstract This study aims to describe character education values in HAMKA’s poems. It used the qualitative descriptive method. The data sources were HAMKA’s 11 poems in his books Kenang-kenangan 70 Tahun Buya HAMKA and Kenang-Kenangan Hidup. The data were collected by reading the content and meaning of each poem carefully and recording them. They were analyzed by the qualitative descriptive technique using Miles and Huberman’s model consisting of research focus identification, data reduction, data analysis and display, and inference making. The results show that HAMKA’s poems contain character education values that include: (1) religiosity, (2) honesty, (3) hard work, (4) autonomy, (5) nationalism spirit, (6) love of the homeland, 7) social care, and (8) responsibility. Through his poems HAMKA tried to convey meaningful messages about the giving of guidance to the reader to become a whole person with characters in the dimensions of heart, mind, body, feeling, and intention. Keywords: character education, poems, HAMKA